Hubungan Penggunaan Media Sosial dan Agresi Verbal Pada Gen Z - Fajar Herlambang Pratama; Tugimin Supriyadi; Rijal Abdillah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of social media has transformed the communication patterns of Generation Z and given rise to various forms of verbal interaction in digital spaces, including verbal aggression. This study aims to examine the relationship between social media use and verbal aggression among Generation Z in Bekasi City. A quantitative method with a correlational design was employed. The research sample consisted of 115 Generation Z respondents who were active social media users, selected using accidental sampling techniques. The research instruments included a social media use scale and a verbal aggression scale. Data analysis was conducted using Pearson’s Product Moment correlation after meeting the assumptions of normality and linearity. The results indicated that there was no significant relationship between social media use and verbal aggression (r = -0.157; p = 0.095; p 0.05). Most respondents were categorized as having high levels of social media use and moderate levels of verbal aggression. These findings suggest that high intensity of social media use is not directly associated with increased verbal aggression among Generation Z. Therefore, the alternative hypothesis was rejected and the null hypothesis was accepted. This study indicates that other factors, such as digital literacy, emotional regulation, and the quality of social interactions, may play a more significant role in influencing verbal aggression than the intensity of social media use alone.